A new cave species of the genus Protaphorura Absolon, 1901 (Collembola, Onychiuridae) from the Western Carpathians (Slovakia) with critical comments to the Palaearctic representatives of the genus - Parimuchová, Andrea; Kováč, Ľubomír (Zootaxa, 2016)
The new species Protaphorura borinensis sp. nov. from a cave of the Western Carpathians, Central Europe, is described. It belongs to congeners with 40 vesicles in PAO and three pseudocelli at the base of antennae and the hind margin of head. P. borinensis sp. nov. has coarse granulation of cuticle on head, and specific distribution of "s" chaetae on abdominal terga and chaetotaxy of ventral tube. Critical comments to the Palaearctic representatives of the genus Protaphorura and an identification key to 85 species are provided.